THE REFORMATION OF THE LOCAL GOVERNMENT AND THE SELF-GOVERNMENT IN UKRAINE: THE PROBLEMS AND THE PERSPECTIVES - Стогова, О.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The article is dedicated to the reformation’s problem of the local government and the self-government in Ukraine. The author analysed categories “decentralization” and “deconcentration” of state authority. For effective functioning of the state, the auther writes, it is necessary to provide a balance of state and local interests. The perspectives of the reformation of the local government and the self-government in Ukraine are analysed.